2012
DOI: 10.1155/2012/137163
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Restore Cell Surface Expression of the Coxsackie Adenovirus Receptor and Enhance CMV Promoter Activity in Castration-Resistant Prostate Cancer Cells

Abstract: Adenoviral gene therapy using the death receptor ligand TRAIL as the therapeutic transgene can be safely administered via intraprostatic injection but has not been evaluated for efficacy in patients. Here we investigated the efficacy of adenoviral TRAIL gene therapy in a model of castration resistant prostate cancer and found that intratumoral injections can significantly delay tumor growth but cannot eliminate established lesions. We hypothesized that an underlying cause is inefficient adenoviral delivery. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…This is possibly because both erbB3 and erbB2 cDNAs are driven by the CMV promoter in the expression vectors, 24, 36 as recent studies show that HDAC inhibitors are capable of enhancing CMV promoter activity. 37, 38 Furthermore, the mammary tumor cell lines 85815 and 85819 derived from MMTV- neu transgenic mice were used to examine the effects of entinostat on endogenous mouse erbB3 and the transgene rat erbB2/neu -encoded protein. Cell growth assays showed that entinostat exhibited potent inhibitory effects on cell proliferation/survival (Figure 2c), similar to that we had observed in human breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…This is possibly because both erbB3 and erbB2 cDNAs are driven by the CMV promoter in the expression vectors, 24, 36 as recent studies show that HDAC inhibitors are capable of enhancing CMV promoter activity. 37, 38 Furthermore, the mammary tumor cell lines 85815 and 85819 derived from MMTV- neu transgenic mice were used to examine the effects of entinostat on endogenous mouse erbB3 and the transgene rat erbB2/neu -encoded protein. Cell growth assays showed that entinostat exhibited potent inhibitory effects on cell proliferation/survival (Figure 2c), similar to that we had observed in human breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the expression of sOPG-Fc inhibits the ability of a CRAd to efficiently lyse infected prostate cancer cells, a panel of prostate cancer cells was infected with Ad5-Δ24-sOPG-Fc-RGD or control viruses. This panel included lines with low levels of CAR expression (C4-2B (40) and PC3 (41)) as well as a line expressing high levels of CAR (LNCaP (42)). After 8 days the monolayers were stained with crystal violet, in a qualitative assay for oncolytic potency.…”
Section: Resultsmentioning
confidence: 99%
“…We observed similar levels of gene expression, viral replication and oncolytic potency between the tropism-modified and wild-type tropism CRAds in these cell lines. The fact that each of these lines expresses CAR, with C4-2B (40) and PC3 cells (41) expressing low but detectable levels and LNCaP cells expressing high levels (42) may explain these results. Although our in vitro experiments did not show a clear advantage in the use of the tropism-modified armed CRAd over its wild-type fiber control, a study by Rauen et al .…”
Section: Discussionmentioning
confidence: 99%
“…We therefore hypothesized that combinations of different inhibitors (e.g., HMN-214 and AG-490) of different kinase targets may show even stronger enhancement than the individual drugs by themselves. We also included the histone deacetylase 1 (HDAC 1) inhibitor Entinostat, which has been shown to enhance transgene expression at concentrations of 10-33 μM [55,56].…”
Section: Enhancement In Transgene Expression Using Combinations Of Inmentioning
confidence: 99%